Regulation of lifespan by chemosensory and thermosensory systems: findings in invertebrates and their implications in mammalian aging - Jeong, Dae-Eun; Artan, Murat; Seo, Keunhee; Lee, Seung-Jae (Frontiers in Genetics, 2012)
Many environmental factors that dynamically change in nature influence various aspects of animal physiology. Animals are equipped with sensory neuronal systems that help them properly sense and respond to environmental factors. Several studies have shown that chemosensory and thermosensory neurons affect the lifespan of invertebrate model animals including Caenorhabditis elegans and Drosophila melanogaster. Although the mechanisms by which these sensory systems modulate lifespan are incompletely understood, hormonal signaling pathways have been implicated in sensory system-mediated lifespan regulation. In this review, we describe findings regarding how sensory nervous system components elicit physiological changes to regulate lifespan in invertebrate models, and discuss their implications in mammalian aging.